2013
DOI: 10.1105/tpc.113.114678
|View full text |Cite
|
Sign up to set email alerts
|

Folate Polyglutamylation Is Involved in Chromatin Silencing by Maintaining Global DNA Methylation and Histone H3K9 Dimethylation in Arabidopsis

Abstract: ORCID ID: 0000-0002-2878-7461 (X-J. H.).DNA methylation and repressive histone Histone3 Lysine9 (H3K9) dimethylation correlate with chromatin silencing in plants and mammals. To identify factors required for DNA methylation and H3K9 dimethylation, we screened for suppressors of the repressor of silencing1 (ros1) mutation, which causes silencing of the expression of the RD29A (RESPONSE TO DESSICATION 29A) promoter-driven luciferase transgene (RD29A-LUC) and the 35S promoter-driven NPTII (NEOMYCIN PHOSPHOTRANSFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 55 publications
(95 reference statements)
9
46
0
Order By: Relevance
“…Tetrahydrofolates present a c-polyglutamyl tail, essential for folate (vitamin B 9 ) metabolism and function. Folate-dependent enzymes generally prefer the polyglutamated formsactually the complete loss of polyglutamation capacity is embryo-lethal (Mehrshahi et al 2010;Zhou et al 2013a)-, while membrane transporters prefer monoglutamyl forms (Suh et al 2001). Because protein-bound folates are protected from hydrolization, the polyglutamyl tail not only regulates their function and compartmentation but also their catabolism (Suh et al 2001).…”
Section: Amino Acids In Vitamin Biosynthesismentioning
confidence: 98%
“…Tetrahydrofolates present a c-polyglutamyl tail, essential for folate (vitamin B 9 ) metabolism and function. Folate-dependent enzymes generally prefer the polyglutamated formsactually the complete loss of polyglutamation capacity is embryo-lethal (Mehrshahi et al 2010;Zhou et al 2013a)-, while membrane transporters prefer monoglutamyl forms (Suh et al 2001). Because protein-bound folates are protected from hydrolization, the polyglutamyl tail not only regulates their function and compartmentation but also their catabolism (Suh et al 2001).…”
Section: Amino Acids In Vitamin Biosynthesismentioning
confidence: 98%
“…The same study demonstrated a release of transcriptional gene silencing in plants treated with methotrexate (MTX). Furthermore, disruption of the plastidial isoform of FPGS in Arabidopsis was reported to result in reduced DNA methylation and release of chromatin silencing at a genome-wide scale (Zhou et al, 2013). …”
Section: Roles Of Folates In Plant Physiologymentioning
confidence: 99%
“…Folate depletion, induced by antifolate drugs or by gene disruption, results in shuttling of C1-units to the synthesis of nucleotides at the expense of methylation reactions (Loizeau et al, 2008). The impairment of the methyl cycle thereafter hinders essential metabolic pathways, such as chlorophyll biosynthesis (Van Wilder et al, 2009), and prevents accurate epigenetic regulation through methylation of DNA and histones (Zhang et al, 2012;Zhou et al, 2013). Also, it is known that Arabidopsis MTHFR performs a reversible reaction and is not feedback inhibited by SAM (Roje et al, 1999).…”
Section: Pp2a-b 0 C Controls a System Of Cross-communicating Metabolimentioning
confidence: 99%